Comparative histological study on wound healing on rat's skin treated with Mitomycin C or Clobetasol propionate - Carvalho,Maria de Fátima Pereira de (2015)
PURPOSE:To compare histologically the action of Mitomycin C and that of Clobetasol propionate for surgical wound healing in rats.METHODS:A circular skin fragment was surgically removed from 57 Wistar rats. Twenty-two animals were treated with Mitomycin C with topical medication in a single dose, 22 with Clobetasol propionate with a cream medication once a day for 15 days and 13 did not receive any medication. The animals were euthanized 30 and 60 days, and the scars subjected to histological examination.RESULTS: The histological analysis on the samples did not show statistically significant differences regarding the quantities of fibroblasts, fibrocytes and vascular proliferation in the three groups, in the evaluations after 30 and 60 days. In the treated groups with Mitomycin C and Clobetasol there was a decrease in collagen concentration over the 30-day period and an increase in collagen concentration over the 60-day period, in comparison with the control group.CONCLUSIONS: The actions of Mitomycin C and Clobetasol were equivalent and not interfere in fibroplasias and in angiogenesis. Both drugs initially cause a decrease in collagen over a 30-day period and an increase over a 60-day period, demonstrating a delay in the wound healing.